Use of ANSYS Software for the Acetabular Cup Structure Analysis out of the Hip Implant - Rashwan, Alkentar (International Journal of Engineering and Management Sciences, 2020)
Modelling the hip implant has been one of the most important researches over the past few decades. In addition, using the ANSYS software for this purpose is well-known procedure to understand the real reaction of the hip implant parts during the daily life of the installed part. This study is to focus on the practical part of the use of ANSYS software to analyse the performance of the hip implant through the feature of structure analysis available in the ANSYS. The research applies the static loads behaviour only with the help of the static structural analysis to view the advantages and the disadvantages of every design, which helps us estimate the implant’s behaviour. The study investigates the optimization of the acetabular cup using the lattice optimization along with the infill option available in the ANSYS software in order to optimize the stress and the fixture of the cup inside the pelvis.